Rethinking Standpoint Epistemology through an Islamic Lens: A Tawhid-Based Reformulation of Objectivity and Knowledge - Silmi, Nadaa Afifah; Arif, Syamsuddin (AJIS: Academic Journal of Islamic Studies, 2025)
Standpoint epistemology, as articulated by Sandra Harding, challenges the claim of neutrality in modern science by situating knowledge within social relations of power. This framework emphasizes the epistemic significance of marginalized social positions as critical sites for revealing structural bias in knowledge production. Despite its extensive discussion within secular feminist theory and philosophy of science, standpoint epistemology has rarely been examined through Islamic epistemological frameworks. This study aims to critically examine Sandra Harding’s standpoint epistemology through the perspective of Islamic epistemology grounded in the principle of tawhid (divine unity). The research employs qualitative conceptual analysis using philosophical-critical methods, examining Harding’s major works in dialogue with the epistemological thought of Syed Muhammad Naquib al-Attas to assess their underlying assumptions, limitations, and epistemic implications. This article makes a conceptual contribution by proposing a tawhid-based reformulation of knowledge that offers a theologically grounded alternative to relativistic epistemic frameworks while retaining the ethical and critical insights of feminist standpoint epistemology.